The Thousand-Year Kingdom: Historical Russia in Russian vampire TV series - E. Yu. Nagaeva (Шаги)
The paper examines the phenomenon of the vampire «new wave» of 2021 – еarly 2022 in the context of cultural policy in Russia. The author focuses on the fact that compared to foreign TV series, the image of a vampire in Russian series is strongly instrumentalized, and a reference to history becomes extremely important in them. In an analysis based on three popular series (Svyatoslav Podgayevsky’s Pischeblok, Anton Maslov’s Central Russia’s Vampires, and Danila Kozlovsky’s Karamora) the author problematizes the representation of history in the newest Russian quasihistorical series. It is argued that a new «commonplace» in the politics of history in Russia is the tendency to create narratives that inconsistently combine the aesthetics of the political regimes of Imperial, Soviet, and contemporary Russia. Thus, a new genealogy of the current sociopolitical order is being constructed, inextricably linking this order with the previous unified tradition. The fantastic figure of the vampire is the keystone of this new narrative. The author suggests that the construction of historical experience is isomorphic to the popular state mythologem of «historical Russia». At the same time, the vampire metaphor vividly embodies not only the idea of the «organic» nature of Russian political power, but also the notion of its necessary transgressiveness.